A conceptual method to simultaneously inhibit methane and hydrogen sulfide production in sewers: The carbon metabolic pathway and microbial community shift. (15th September 2019) - Ai, Tao; He, Qiang; Xu, Jingwei; Yin, Feixian; Li, Hong; Ai, Hainan
Abstract: In this study, the impact of COD/SO4 2− ratio in sewage on methane and hydrogen sulfide production in sewer biofilms was investigated by using three identical lab-scale gravity sewer systems. The results showed that the COD/SO4 2− played a key role in the competition between methanogenic archaea (MA) and sulfate reducing bacteria (SRB). Both the lowest methane and hydrogen sulfide production were obtained at COD/SO4 2− ratio of 6. The carbon transformation revealed that the activity of both MA and SRB was inhibited at this COD/SO4 2− ratio. Methanosarcina and Methanobacterium were the two dominant MA, while Desulfonema, Desulfotomaculum and Desulfovibrio were the dominant SRB in this case. The specific SRB activity measured by batch tests proved that acetate was mainly degraded by the MA, while propionate was the preferred substrate for the SRB. Graphical abstract: Image 1 Highlights: The anabolism of SRB inhibited the MA to produce methane at COD/SO4 2− ratio of 6. Difference of carbon metabolic pathway was observed at different COD/SO4 2− ratios. The COD/SO4 2− ratio would affect the assimilation and dissimilation of COD by MA and SRB.